PENGARUH PENERAPAN CORPORATE GOVERNANCE, DPK, CAR DAN NPL TERHADAP PROFITABILITAS BANK - Wantera, Ni Luh Kunthi Pranyanti Sentana Madri; Mertha, I Made (E-Jurnal Akuntansi, 2015)
National development in economic sector cannot be rid of financial institution, in this case is bank which is an intermediation institution in public. Bank in their financial activities trade on trust from the public and others party like stock holder. In that case, bank needs to keep stabilized moreover increase their financial performance. One of financial achievement standard that have been achieve by the company can be refer to their profitability. The purpose on this studies are to determine the effect of corporate governance, third party fund, capital adequacy ratio and non performing loan to bank profitability. The sample on this studies are the banking company that have been listed on the Indonesia Stock Exchanged (IDX) and include in the Corporate Governance Perception Indeks (CGPI) ranking between 2009 until 2013, totally 31 samples. The profitability on this studies can be measured by return on asset (ROA). The result show that third party fund, capital adequacy ratio (CAR) and non performing loan (NPL) have significant effect to bank profitability. The corporate governance on this studies have not significant effect to bank profitability.
Keywords: Bank profitability, corporate governance, third party fund, car, npl